1993
DOI: 10.1083/jcb.123.4.977
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-cytoskeletal interactions in migrating fibroblasts are dynamic, asymmetric, and regulated.

Abstract: Abstract. We have used laser optical trapping and nanometer-level motion analysis to investigate the cytoskeletal associations and surface dynamics of/31 integrin, a cell-substrate adhesion molecule, on the dorsal surfaces of migrating fibroblast cells. A singlebeam optical gradient trap (laser tweezers) was used to restrain polystyrene beads conjugated with anti-/5'l integrin mAbs and place them at desired locations on the cell exterior. This technique was used to demonstrate a spatial difference in integrin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
190
2
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(203 citation statements)
references
References 49 publications
10
190
2
1
Order By: Relevance
“…The chronic application of these devices has been limited by their unpredictable failure over extended periods. Although the precise mechanism for this failure is not completely known, it is suggested that an undesirable brain tissue reaction to the device leads to the formation of a glial scar which then serves as a barrier to neural signal transduction [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The chronic application of these devices has been limited by their unpredictable failure over extended periods. Although the precise mechanism for this failure is not completely known, it is suggested that an undesirable brain tissue reaction to the device leads to the formation of a glial scar which then serves as a barrier to neural signal transduction [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In motile cells, mechanical tension at sites of cell adhesion stimulates the assembly of macromolecular protein complexes at the membrane junctions between the extracellular matrix and the actin cytoskeleton (18,37,53,111). Proteins bound within these adhesion complexes are in a constant state of dynamic exchange with their cytoplasmic pools, where they may exist in an inactive state.…”
Section: Contractile Stimulation Catalyzes the Assembly Of Macromolecmentioning
confidence: 99%
“…Models for the regulation of actin dynamics in migrating cells can provide a template for a mechanistic model for the regulation of actin polymerization in smooth muscle tissues during contraction (55,79,102). During cell migration, mechanical tension at sites of membrane extension at the leading edge of the cell induces integrin clustering and activation, the recruitment of cytoskeletal adhesion and signaling proteins to sites of cell adhesion, and the polymerization of actin filaments, resulting in extension of the cell membrane and cell crawling (39,86,111).…”
Section: Activation Of the Arp2/3 Complex By Wasp Family Proteins Regmentioning
confidence: 99%
“…Two studies have visualized integrins undergoing directed movement in protrusions. One tracks them to the leading edge (Schmidt et al 1993), and the other shows them associated with actin "comet tails" moving across the leading edge (Galbraith et al 2007). Although there is evidence that integrins cycle from the rear (Lawson and Maxfield 1995), it is not clear that this is a general mechanism.…”
Section: Integrins In Cell Migrationmentioning
confidence: 99%